The Effect of Mother-Infant Skin to Skin Contact after Birth on Third Stage of Labor: A Systematic Review and Meta-Analysis - Fatemeh Zahra KARIMI; Hamid HEIDARIAN MIRI; Maryam SALEHIAN; Talat KHADIVZADEH; Mohaddese BAKHSHI (Tehran University of Medical Sciences, 2019)
Background: One of the causes of postpartum hemorrhage is prolongation of third stage of labor. Mother-infant skin to skin contact (SSC) immediately after delivery is one of the non-pharmacological interventions to reduce this stage. Studies which assessed the effect of mother-infant SSC after delivery on duration of the third stage of labor reported controversial results on this issue. Therefore, this study investigated the effect of mother-infant SSC immediately after birth on the duration of third stage of labor Methods: In this systematic review and meta-analysis, the databases of PubMed, Scopus, Cochrane, SID, Magiran IranDoc and Google Scholar were searched from 2000 to 2018, using the keywords related to the objectives of this review to access randomized control trials published in Persian or English. The quality of papers was examined using Cochran's Risk of bias tool. Data was analyzed using Stata software. We used I2 index and Chi-square test to investigate heterogeneity and Egger's and Begg's tests to assess publications bias. Random effects model was used to combine the data. Results: Six studies were entered into the meta-analysis. The third stage of labor in SSC group was shorter than that of control group with a mean difference of -1.33 and 95% CI (-2.31 to -0.36) and this difference was statistically significant (P=0.007). Conclusion: Mother-infant SSC decreases the duration of third stage of labor. Therefore, the current study provides some evidences to use this non-pharmacological method in order to accelerate the third stage of labor and ultimately prevent postpartum hemorrhage.